Ceratocystis eucalypticola sp. nov. from Eucalyptus in South Africa and comparison to global isolates from this tree - M. van Wyk; J. Roux; G. Kamgan Nkuekam; B.D. Wingfield; M.J. Wingfield (IMA Fungus)
Eucalyptus trees, mostly native to Australia, are widely planted in the tropics and Southern Hemisphere for the production of wood and pulp. Worldwide surveys of diseases on these trees have yielded a large collection of Ceratocystis isolates from dying trees or from wounds on their stems. The aim of this study was to characterise these isolates and to consider their relatedness to each other. Culture appearance, morphological features and a distinctive fruity odour in all cultures were typical of species in the Ceratocystis fimbriata sensu lato (s. lat.) complex. Phylogenetic analyses of sequences for the combined ITS, βt-1 and TEF1-α gene regions revealed a genetically diverse group of isolates residing in a single large clade, that were distinct from all other species in the C. fimbriata s. lat. complex. Based on morphology and phylogenetic inference, the Eucalyptus isolates are recognised as closely related. The South African isolates are described here as a new species, C. eucalypticola.